Genome-wide association study identified ATP6V1H locus influencing cerebrospinal fluid BACE activity - Hao Hu; Haiyan Li; Jieqiong Li; Jintai Yu; Lan Tan; Alzheimer's Disease Neuroimaging Initiative (BMC, 2018)
Abstract Background The activity of cerebrospinal fluid (CSF) β-site APP cleaving enzyme (BACE) is a potential diagnostic biomarker for Alzheimer disease (AD). Methods A total of 340 non-Hispanic Caucasian participants from the Alzheimer's Disease Neuroimaging Initiative cohort (ADNI) database were included in this study with quality-controlled CSF BACE and genotype data. Association of CSF BACE with the genetic variants of single nucleotide polymorphisms (SNPs) was assessed using PLINK under the additive genetic model. The P values of all SNPs for CSF BACE were adjusted for multiple comparisons. Results One SNP (rs1481950) in the ATP6V1H gene reached genome-wide significance for associations with CSF BACE (P = 4.88 × 10− 9). The minor allele (G) of rs1481950 was associated with higher CSF BACE activity. Although seven SNPs in SNX31, RORA, CDH23, RGS20, LRRC4C, MAPK6PS1 and LOC105378355 did not reach genome-wide significance (P < 10− 8), they were identified as suggestive loci (P < 10− 5). Conclusion This study identified rs1481950 within ATP6V1H influencing human CSF BACE activity, which indicated that ATP6V1H gene may play some roles in the pathogenesis of neurodegenerative diseases such as AD.